2016
DOI: 10.1021/acs.macromol.6b00317
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hierarchical Ordering in Supramolecules via Symmetrically Bifunctionalized Organic Semiconductor

Abstract: Block copolymer (BCP)-based supramolecular systems provide a versatile approach to manipulate functional structures spanning several nanometers to macroscopic length scales. Most studies to date focused on supramolecules containing asymmetrically end-functionalized small molecules, and it remains challenging to obtain molecular control over small molecule ordering within the BCP microdomain. Here we designed symmetrically end-functionalized bis-phenol quarter­thiophene (BP4T) small molecules and systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…observed that the presence of the LC side group could promote the phase separation of styrene–methacrylate BCPs due to the positive contribution of the LC group to the Flory–Huggins parameter χ between different segments. , In addition, Deepthi et al found that the morphology changed from hexagonally packed cylinders (HEX) to lamellae (LAM) upon adding naphthalene diimide (NDI) to poly­(styrene- b -4-vinylpyridine) (PS- b -P4VP), which was attributed to the increased overall volume fraction of P4VP microdomains after complexation of NDI with the P4VP block . Moreover, the order-to-disorder transition (ODT) of the LC structure within one block may also induce the order-to-order transition (OOT) or ODT of BCPs. , It is also reported that the crystallization of incompatible side chains may alter the periodicity and ordering of the large-scale structure of BCPs . On the other hand, the microphase-separated structure at the first level may also influence the third-level structure.…”
Section: Introductioncontrasting
confidence: 61%
See 1 more Smart Citation
“…observed that the presence of the LC side group could promote the phase separation of styrene–methacrylate BCPs due to the positive contribution of the LC group to the Flory–Huggins parameter χ between different segments. , In addition, Deepthi et al found that the morphology changed from hexagonally packed cylinders (HEX) to lamellae (LAM) upon adding naphthalene diimide (NDI) to poly­(styrene- b -4-vinylpyridine) (PS- b -P4VP), which was attributed to the increased overall volume fraction of P4VP microdomains after complexation of NDI with the P4VP block . Moreover, the order-to-disorder transition (ODT) of the LC structure within one block may also induce the order-to-order transition (OOT) or ODT of BCPs. , It is also reported that the crystallization of incompatible side chains may alter the periodicity and ordering of the large-scale structure of BCPs . On the other hand, the microphase-separated structure at the first level may also influence the third-level structure.…”
Section: Introductioncontrasting
confidence: 61%
“…28,29 It is also reported that the crystallization of incompatible side chains may alter the periodicity and ordering of the large-scale structure of BCPs. 30 On the other hand, the microphase-separated structure at the first level may also influence the third-level structure. For example, Hamley et al observed that the LC ordering of the side groups was suppressed in a BCP with a high fraction of the amorphous block.…”
Section: ■ Introductionmentioning
confidence: 56%
“…Low-molecular-weight additives that associate with one of the blocks of a BCP by noncovalent interactions afford a simple strategy to introduce new functionality and provide a simple route to fine-tune the morphology by solvent and/or thermal annealing. These annealing processes, although, are energy-intensive, environmentally unfriendly, and make processing more complex, limiting the fabrication of large-scale films. Ideally, the additive would serve to significantly enhance the microphase separation and mediate interfacial interaction so as to promote the orientation of the microdomains normal to the surface of the film, thereby eliminating postprocessing steps.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to create these ordered crystalline domains in the supramolecular thermoplastics is based on the modification of end‐groups of low molecular weight telechelic polymers with multiple hydrogen bonding dynamic motifs that “stick” together and assemble into a supramolecular network in the solid state . Another technique to design a more sophisticated supramolecular architecture in the polymer matrix utilizes dynamic‐bonding interactions between the polymer end‐group or side chain of block copolymers and small molecules. It is a challenge to make these materials have stimuli‐responsive properties, however, since the key design feature of this class of supramolecular materials is based on complex interactions of multiple hydrogen‐bonding motifs, which suffer from non‐ideal photochemical properties such as a lack of visible light absorption.…”
Section: Introductionmentioning
confidence: 99%